Promoter methylation of cancer-related genes in gastric carcinoma - Poplawski, T.; Tomaszewska, K.; Galicki, M.; Morawiec, Z.; Blasiak, J. (Experimental Oncology, 2008)
Genetic changes associated with gastric cancer are not completely known, but epigenetic mechanisms involved in this disease seem to play an important role in its pathophysiology. One of these mechanisms, an aberrant methylation in the promoter regions of genes involved in cancer induction and promotion, may be of particular importance in gastric cancer. Aim: To analyze the methylation status of eight genes: Apaf-1, Casp8, CDH1, MDR1, GSTP1, BRCA1, hMLH1, Fas in gastric cancer patients. Methods: The methylation pattern of the genes was assessed by methylation specific restriction enzyme PCR (MSRE-PCR) in gastric tumors taken during surgery of 27 patients and compared with the methylation pattern in material obtained from biopsy in 25 individuals without cancer and pre-cancerous lesions. Results: We observed a promoter hypermethylation in the Casp8, hMLH1, CDH1 and MDR1 in gastric cancer patients as compared with the controls. Additionally, we investigated the relationship between promoter hypermethylation and age, gender, smoking and gastric cancer family history. The hypermethylation of the hMLH1 gene occurred more frequently in female than in men, and the hypermethylation of the CDH1 gene was observed preferentially in smoking than in non-smoking individuals. Conclusion: The data obtained indicate that changes in DNA methylation may contribute to gastric carcinogenesis. Генетические изменения, ассоциированные с опухолью желудка, изучены не в полной мере. В то же время эпигенетические механизмы скорее всего играют ключевую роль и лежат в основе возникновения этого заболевания. Один из таких механизмов– нарушенияметилирования промоторов генов, которые регулируют злокачественнуютрансформациюи прогрессирование опухолевого процесса, может быть особенно важным в развитии рака желудка. Цель: проанализировать статус метилирования промоторов восьми генов: Apaf-1, Casp8, CDH1, MDR1, GSTP1, BRCA1, hMLH1, Fas у больных раком желудка. Методы: метилирование промоторов генов изучали с помощьюспецифической к сайтамметилирования рестрикцией с ПЦР (MSRE-PCR) на хирургическомматериале (опухоли желудка) 27 пациентов. Вкачестве контроля использовали иопсийныйматериал, полученный от 25 больных, у которых не было выявлено рака или предраковых состояний. Результаты: отмечали гиперметилирование промоторов генов Casp8, hMLH1, CDH1 и MDR1 в опухолевой ткани желудка по сравнению с контрольными образцами. Кроме того, нами была прослежена взаимосвязь между гиперметилированием промоторов генов и возрастом, полом пациентов, курением и семейной историей заболевания раком желудка. Гиперметилирование гена hMLH1 выявляли чаще у женщин, чем у мужчин, а гиперметилирование гена CDH1 — в основном у курильщиков. Выводы: полученные данные свидетельствуют о том, что метилирование ДНК может играть важную роль при развитии рака желудка.